Orphan: First kill [videorecording (Blu-Ray)] - Fuhrman, Isabelle, 1997-; Stiles, Julia, 1981-; Sutherland, Rossif, 1978-; Coggeshall, David (Paramount, 2022)
Esther's terrifying saga continues in this thrilling prequel to the original and shocking horror hit "Orphan." After orchestrating a brilliant escape from an Estonian psychiatric facility, Esther travels to America by impersonating the missing daughter of a wealthy family. Yet, an unexpected twist arises that pits her against a mother who will protect her family from the murderous "child" at any cost.